2015
DOI: 10.1007/s11745-015-4070-4
|View full text |Cite
|
Sign up to set email alerts
|

Forms of n‐3 (ALA, C18:3n‐3 or DHA, C22:6n‐3) Fatty Acids Affect Carcass Yield, Blood Lipids, Muscle n‐3 Fatty Acids and Liver Gene Expression in Lambs

Abstract: The effects of supplementing diets with n-3 alpha-linolenic acid (ALA) and docosahexaenoic acid (DHA) on plasma metabolites, carcass yield, muscle n-3 fatty acids and liver messenger RNA (mRNA) in lambs were investigated. Lambs (n = 120) were stratified to 12 groups based on body weight (35 ± 3.1 kg), and within groups randomly allocated to four dietary treatments: basal diet (BAS), BAS with 10.7 % flaxseed supplement (Flax), BAS with 1.8 % algae supplement (DHA), BAS with Flax and DHA (FlaxDHA). Lambs were fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 39 publications
2
27
0
Order By: Relevance
“…However, PUFAs are more susceptible to lipid peroxidation due to their double bond content, rendering them more accessible to free radicals and ROS, [18] which can result in cellular impairment. [20,21] In the present study, we found that high-dose ALA can affect lipid metabolic gene expression in adipocytes. In addition, we also found that polyphenol compounds can alleviate high-dose PUFA-induced oxidative damage in adipocytes.…”
Section: Discussionsupporting
confidence: 56%
“…However, PUFAs are more susceptible to lipid peroxidation due to their double bond content, rendering them more accessible to free radicals and ROS, [18] which can result in cellular impairment. [20,21] In the present study, we found that high-dose ALA can affect lipid metabolic gene expression in adipocytes. In addition, we also found that polyphenol compounds can alleviate high-dose PUFA-induced oxidative damage in adipocytes.…”
Section: Discussionsupporting
confidence: 56%
“…Their effects on plasma FA have been studied using different methodological approaches, either by analyzing the FA profile in total plasma or in lipids or lipoprotein classes of plasma, or by quantification of lipid classes by enzymatic analyses. Using the latter method, the available data report discrepancies in the responses of the lipid class concentrations to diets supplemented with lipids . Otherwise, when the total FA in plasma was considered, it did not give FA location information on the different plasma lipid species.…”
Section: Effects Of Dietary Lipids On Lipid Metabolism In Dairy Ruminmentioning
confidence: 99%
“…Animals fed forage‐based rations have been reported in some studies to produce meat with a lower glycogen content in muscle tissue and thus a higher ultimate pH and darker color than meat from lambs fed concentrate‐based rations (Young and others ). This has been mainly attributed to the lower energy intake by the animals associated with loss of dietary energy, such as gas that is associated with degradation of high‐fibrous roughage materials (Ponnampalam and others ). Furthermore, such animals spend more energy during grazing as they comparatively walk longer distances to harvest their food (Aguayo‐Ulloa and others ) and this higher level of exercise leads to producing less fat there will be less reflectance of light (Díaz and others ).…”
Section: The Effect Of Forage‐based Systems On Lamb Productionmentioning
confidence: 99%